Republic of Korea : Financial Sector Assessment Program-Technical Note-Insolvency and Creditor Rights. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
The Korean insolvency and creditor rights framework is complex and has undergone several reforms in recent years. Consistent efforts to enhance the efficiency and effectiveness of the insolvency system have been made since the Asian crisis by the multiple government agencies that oversee the functioning of the insolvency framework in Korea. This note summarizes the key findings of the analysis of select aspects of the Korean insolvency and creditor rights system against the international standard.2 While the framework for personal insolvency is also discussed (See Annex), its analysis is not prescriptive, as there are no international best practices in this area.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet